2011
DOI: 10.1007/s00784-011-0632-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of marginal and internal adaptation after occlusal stressing of indirect class II composite restorations with different resinous bases and interface treatments. “Post-fatigue adaptation of indirect composite restorations”

Abstract: The present study evaluated the influence of different composite bases and surface treatments on marginal and internal adaptation of class II indirect composite restorations, after simulated occlusal loading. Thirty-two class II inlay cavities were prepared on human third molars, with margins located in cementum. A 1-mm composite base extending up to the cervical margins was applied on all dentin surfaces in the experimental groups; impressions were made and composite inlays fabricated. The following experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…marginal adaptation compared to rigid materials, while Rocca et al [21] found that composite type exerted no significant influence on marginal adaptation. Furthermore, the application of three consecutive 1-mm-thick layers of a highly filled restorative composite provided the best marginal quality to dentin, whereas self adhesive resin cements performed significantly more poorly [11].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…marginal adaptation compared to rigid materials, while Rocca et al [21] found that composite type exerted no significant influence on marginal adaptation. Furthermore, the application of three consecutive 1-mm-thick layers of a highly filled restorative composite provided the best marginal quality to dentin, whereas self adhesive resin cements performed significantly more poorly [11].…”
Section: Discussionmentioning
confidence: 97%
“…According to recent in vitro studies performed on non-endodontically treated molars, PBE did not necessarily influence the marginal adaptation compared to indirect restorations without the placement of a proximal composite base [11,12,21]. However, there are currently no data available regarding how composite bases in deep sub-gingival areas impact the marginal quality and fracture behavior of root canal filled teeth with indirect restorations.…”
Section: Introductionmentioning
confidence: 99%
“…During the first phase, all of the restorations were subjected to a thermo-mechanical cycling loading in a computer-controlled masticator. In order to mimic invivo testing conditions, the low masticatory force of 49 N was applied for 600 000 cycles at 1.7 Hz, corresponding to approximately 2.5 years of mild clinical function (without peaks) in premolar region [20][21][22]. A more clinically relevant number of cycles of 10 6 at low masticatory loads -corresponding to approximately 5 years of function -has been suggested before [23].…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have evaluated methods for removal of provisional cement in vitro. Reviewing these studies, it was found that the highest bond strength values were reported with soft-air abrasion (ROCCA et al, 2012), airborne particle abrasion with aluminum oxide (DILLENBURG et al, 2009. MAGNE et al, 2007.…”
Section: Discussionmentioning
confidence: 99%